2003
DOI: 10.1016/s0925-4005(03)00175-8
|View full text |Cite
|
Sign up to set email alerts
|

Gas-sensitive properties of thin film heterojunction structures based on Fe2O3–In2O3 nanocomposites

Abstract: This paper reports an investigation of the gas-sensitive properties of thin film sensors based on the double-layers Fe 2 O 3 -In 2 O 3 and Fe 2 O 3 -In 2 O 3 /In 2 O 3 towards gases of different chemical nature (C 2 H 5 OH, CH 4 , CO, NH 3 , NO 2 , O 3 ). As it was found, the g-Fe 2 O 3 -In 2 O 3 composite (Fe:In ¼ 9:1, mol) is more sensitive to O 3 ; on the contrary, the a-Fe 2 O 3 -In 2 O 3 (9:1) system, possesses a higher sensitivity to NO 2 . The optimal temperature for detecting of both gases is in the ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 87 publications
(31 citation statements)
references
References 9 publications
0
31
0
Order By: Relevance
“…Iron oxide, metal oxide semiconducting material, can exist in various forms such as α-Fe 2 O 3 , γ-Fe 2 O 3 and Fe 3 O 4 . The gas sensing properties of α & γ forms are still not established and contrasts are available in Iron oxide literature [1,2]. Some papers attribute to gas-sensing properties of γ-Fe 2 O 3 and Fe 3 O 4 rather than to α-Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Iron oxide, metal oxide semiconducting material, can exist in various forms such as α-Fe 2 O 3 , γ-Fe 2 O 3 and Fe 3 O 4 . The gas sensing properties of α & γ forms are still not established and contrasts are available in Iron oxide literature [1,2]. Some papers attribute to gas-sensing properties of γ-Fe 2 O 3 and Fe 3 O 4 rather than to α-Fe 2 O 3 .…”
Section: Introductionmentioning
confidence: 99%
“…Some papers attribute to gas-sensing properties of γ-Fe 2 O 3 and Fe 3 O 4 rather than to α-Fe 2 O 3 . The α-Fe 2 O 3 form has been recognized as having minimal gas-sensing response [1] It has been reported that the thermal stability of the γ-Fe 2 O 3 limits its use as gas sensor [2] Iron titanium oxide solid solutions have shown response to ethanol [3]. Some report says α-Fe 2 O 3 , the most stable iron oxide with n-type semiconducting properties under ambient conditions, is extensively used as gas sensor, catalysts [4,[5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…There are a few scattered reports which discuss the potential of iron oxide as a gassensing material [8][9][10][11][12][13][14][15][16][17]. Iron oxide can exist in various forms such as ␣-Fe 2 O 3 , ␥-Fe 2 O 3 and Fe 3 O 4.…”
Section: Introductionmentioning
confidence: 99%
“…Iron oxide can exist in various forms such as ␣-Fe 2 O 3 , ␥-Fe 2 O 3 and Fe 3 O 4. The gas-sensing properties of the ␣ and ␥ forms are still not established and contrasts are available in literature [10,15]. Some reports attribute the gas-sensing properties of iron oxides to ␥-Fe 2 O 3 or Fe 3 O 4 forms rather than to ␣-Fe 2 O 3.…”
Section: Introductionmentioning
confidence: 99%
“…However, they suffer from many problems: high working temperatures and high threshold values compared to atmospheric pollution concentrations. Many metal oxides gas sensors can be also used; such as tin oxide (SnO 2 ) [8,9], indium oxide (In 2 O 3 ) [10][11][12][13] or tungsten oxide (WO 3 ) [14][15][16][17]. In general, they show high sensitivity and reproducible results, but they need work at elevated temperatures.…”
Section: Introductionmentioning
confidence: 99%